Constrained adoptive parenthood and family transition: adopters' experience of unplanned birth family contact in adolescence. Issue 1 (3rd January 2013) - MacDonald, Mandi; McSherry, Dominic
Abstract Adoption policy in the UK emphasizes its role in providing secure, permanent relationships to children in care who are unable to live with their birth families. Adoptive parents are crucial in providing this life‐long, stable experience of family for these vulnerable children. This paper explores the experience of adoptive parenthood in the context of changes to adoptive kinship relationships brought about by new, unplanned contact with birth family during their child's middle adolescence. This contact was initiated via informal social networks and/or social media, with older birth siblings instrumental in negotiating renewed relationships. The contact precipitated a transition in adoptive family life resulting in emotional challenges and changes in parent/child relationships, which were experienced as additional to the normative transitions expected during adolescence. Parental concern as a dominant theme was founded in the child and birth sibling's stage of adolescence, coupled with constraints on adoptive parenthood imposed by the use of social media, by perceived professional attitudes and by parental social cognitions about the importance of birth ties. Adoptive parents' accounts are interpreted with reference to family life‐cycle theory and implications are suggested for professional support of adoptive kinship relationships.